2017
DOI: 10.1021/jacs.7b06130
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering a Single-Protein Junction

Abstract: Bioelectronics moves toward designing nanoscale electronic platforms that allow in vivo determinations. Such devices require interfacing complex biomolecular moieties as the sensing units to an electronic platform for signal transduction. Inevitably, a systematic design goes through a bottom-up understanding of the structurally related electrical signatures of the biomolecular circuit, which will ultimately lead us to tailor its electrical properties. Toward this aim, we show here the first example of bioengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(162 citation statements)
references
References 89 publications
3
159
0
Order By: Relevance
“…Our main finding is that quantum coherent effects are prevalent, and they play a central role in biological electron transport over the distance of few nanometers. It is interesting to explore similar questions of electron transfer through proteins [71].…”
Section: Discussionmentioning
confidence: 99%
“…Our main finding is that quantum coherent effects are prevalent, and they play a central role in biological electron transport over the distance of few nanometers. It is interesting to explore similar questions of electron transfer through proteins [71].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Among them, redox-active molecules could be converted between the oxidized and reduced states upon different electrochemical potentials, and have been widely studied to illustrate the electrochemical gating at single-molecule level, such as ferrocene, [8] pyrrolo-tetrathiafulvalene, [9] anthraquinone, [10] viologen, [11] transition metal complex [8a,12] and redox-active DNA or proteins. [13] Their conductance could switch on as the energy level of electrodes shifted to resonance with molecules. With this unique family of redox-active molecules, ongoing interest is to obtain a high on/off ratio of conductance.…”
Section: Improving Gating Efficiency Of Electron Transport Through Rementioning
confidence: 99%
“…[1,2] Thea bility to rationally design protein-based electrical components,r equires fundamental understanding of their charge-transport mechanism. [1,3,4] Ear-lier studies have shown that the characteristics of electronic charge transport, ETp,via protein junctions are influenced by the protein structure, [5][6][7] electrode-protein coupling, [8][9][10] and the alignment of frontier molecular orbital energies with respect to the Fermi levels (E F )o ft he electrode, [11,12] often characterized by as ingle parameter known as the energy barrier. [13] Thec ombination of protein molecular orbitals and their coupling to the electrodes dictates the transmission probability across the junction.…”
Section: Introductionmentioning
confidence: 99%